CONVERTING AGRICULTURE FROM A CURSE TO A BLESSING CATHOLIC ORGANIC RICE FARMERS IN INDONESIA - Sri Winarsih, Fransisca Yohana; Putra, Heddy Shri Ahimsa; Bagir, Zainal Abidin; Northcott, Michael Stafford (Journal of Asian Orientation in Theology, 2024)
Since the 1960s, Indonesia has pursued Green Revolution routes that rely on agrochemical methods to increase rice yields. As soil quality declines and costs of artificial fertilizer and hybrid seeds rise, some farmers have adopted organic rice farming methods. Several studies of this trend have been published, but only a few have explored the role of religion in this gradual move to organic farming. This ethnographic study of eight Catholic farmers in Yogyakarta Special Region/Daerah Istimewa Yogyakarta (DIY), Central Java Province, and East Nusa Tenggara Province/Nusa Tenggara Timur (NTT) reveals that while increasing costs of inputs are a factor in conversion, religious perspectives on food and the environment also played a role. The study utilizes the constructivism-interpretivism paradigm and the concept of 'Religion in everyday life' by Nancy Ammerman. The interview reveals that religion is present in faith in God(s), a sense of interconnectedness, a sense of purpose, emotion, spiritual narrative, embodiment, and virtues. Given the highly religious character of Indonesia, this pilot study indicates the need for further research on the role of religion in agricultural development, particularly in the move towards more ecological farming.